Students' Perspectives on Inclusive Education in Indonesia: Insights from a Systematic Literature Review - Rini, Thalia Ayu; Azizah, Nur (Indonesian Journal of Educational Research and Review, 2024)
The implementation of inclusive education in Indonesia indicates a tendency toward favourable outcomes in providing better quality educational services for children with special needs. In order to enhance the efficacy and advancement of inclusive education in Indonesia, it is crucial to consider the perspectives of students towards inclusive education. Hence, this PRISMA-compliant literature review examines relevant studies on Indonesian students' perspectives on inclusive education. The chosen publication is a Scopus-indexed journal article or conference proceeding on empirical research. The Scopus and ERIC databases yielded five relevant studies. Findings showed that students with and without special needs have positive and negative perspectives. Positively, inclusive education students value teacher and peer support, a sense of belonging, friendship, and self-determination. Conversely, students' negative perspectives include academic challenges, social isolation, stigmatization, and bullying in inclusive schools. To fully understand student perspectives, the authors recommend further longitudinal or comparative research with a broader and more diverse population of students with special needs.